2016
DOI: 10.1007/s00204-016-1689-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress modulation of hepatocyte-like cell function

Abstract: Freshly isolated human adult hepatocytes are considered to be the gold standard tool for in vitro studies. However, primary hepatocyte scarcity, cell cycle arrest and the rapid loss of cell phenotype limit their widespread deployment. Human embryonic stem cells and induced pluripotent stem cells provide renewable sources of hepatocyte-like cells (HLCs). Despite the use of various differentiation methodologies, HLCs like primary human hepatocytes exhibit unstable phenotype in culture. It has been shown that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 29 publications
6
79
0
Order By: Relevance
“…To investigate the effect of continuous shear stress on the metabolism, gene expression and mechanical phenotype of the static condition were compared with those of OS (70 rpm) and rotational SFU (6 rpm). We showed that under the presence of DMSO and serum, mild shear stress (0.032 Pa from SFU) exerted positive effects on hepatic differentiation and metabolic activities compared with other operation modes (static and OS; Figures and S3), which corresponded to previously reported studies (Rashidi, Alhaque, Szkolnicka, Flint, & Hay, ; Semenova et al, ; Torii et al, ; Vinci et al, ). However, this upregulated state, in the case of the SFU mode, was not maintained during the 3‐day adaptation process (culture without DMSO in the presence of serum and mode operation), but resulted in the deterioration of hepatic functionality (CYP3A4 activity, Figure a; albumin production, Figure b), drug metabolism capability of spheroids (Figure c).…”
Section: Discussionsupporting
confidence: 89%
“…To investigate the effect of continuous shear stress on the metabolism, gene expression and mechanical phenotype of the static condition were compared with those of OS (70 rpm) and rotational SFU (6 rpm). We showed that under the presence of DMSO and serum, mild shear stress (0.032 Pa from SFU) exerted positive effects on hepatic differentiation and metabolic activities compared with other operation modes (static and OS; Figures and S3), which corresponded to previously reported studies (Rashidi, Alhaque, Szkolnicka, Flint, & Hay, ; Semenova et al, ; Torii et al, ; Vinci et al, ). However, this upregulated state, in the case of the SFU mode, was not maintained during the 3‐day adaptation process (culture without DMSO in the presence of serum and mode operation), but resulted in the deterioration of hepatic functionality (CYP3A4 activity, Figure a; albumin production, Figure b), drug metabolism capability of spheroids (Figure c).…”
Section: Discussionsupporting
confidence: 89%
“…The ability to differentiate iPSCs to hepatocyte-like cells (HLCs) with appropriate drug metabolizing capacities789, has made general toxicity assessments on these liver-derived cells feasible1011121314. HLCs have been extensively characterized15 which has led to their improved functionality as drug-metabolizing cells1617. Still, the demonstration of iPSC-derived HLCs as models for idiosyncratic hepatotoxicity has thus far lacked clear clinical relevance and has been limited to metabolic variations attributable to single well-characterized cytochrome P450 variants18 or to the observation of donor-dependent differences in drug toxicity screens19.…”
mentioning
confidence: 99%
“…Fluid shear also has substantial biochemical and ultrastructural effects on renal cells [2024]. Shear stress reintroduced into hemodynamic flow systems maintains the expression of certain CYPs [17, 25]. When rat hepatocytes in monolayers were exposed to 0.6 dyne/cm 2 of shear stress in a perfused Transwell device, CYP1A1 increased 54-fold, CYP1A2 increased 64-fold, CYP2B1 increased 15-fold, and, most importantly for the thesis of this review, CYP2B2 increased threefold relative to static cultures [17].…”
Section: Strategies To Introduce Physiologic Levels Shear Stress Imentioning
confidence: 99%